Snow Like Ashes - Book 1 - Raasch, Sara (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2014)
Orphaned Meira, a fierce chakram-wielding warrior from the Kingdom of Winter, must struggle to free her people from the tyranny of an opposing kingdom while also protecting her own destiny.
Accelerated Reader AR